Social factors of under-five mortality in rural Agra - Kumar, Krishan; Srivastava, Rajiv; Mishra, S. K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Very limited recent data is available on the causes of child deaths in India.Most of the available studies do not accurately reflect the socio factors related to these deaths. Identifying and assessing the factors affecting the child mortality could be the first step in planning to reduce the mortality and promoting the society health and life expectancy. Therefore the present study was undertaken to find out the socio factors of deaths among children under 5 years of age. Methods: The present cross-sectional survey was conducted among under five children and their parents residing within the selected villages in a community Development Block Sainyan, District Agra using Multistage random sampling technique. Participatory learning action technique was used. Data was analyzed and presented in form of percentages. Results: Diarrhoea was the most common cause of under five children mortality followed by acute respiratory tract infection and pyrexia. Delay in recognition of problem followed by delay in decision making at family level, delay in seeking of health provider and delay in arranging transport were the main social causes of deaths. Most children were attended by local rural medical practitioners both at initial and terminal stages of illness. Conclusions: Efforts to prevent diarrhoea and acute respiratory tract infection must be intensified. Awareness about the services provided by the government and their utilization should be strengthened.